Comparison of Efficacy of Empagliflozin Versus Dapagliflozin in Type 2 Diabetes Among Inadequately Controlled on Metformin/Glemipride/DPP4 at a Tertiary Care Hospital - Sajid, Muhammad; Khan, Humayun Riaz; Muzaffar, Muhammad; Zafar, Muhammad (Biological and Clinical Sciences Research Journal, 2025)
Sodium–glucose cotransporter-2 (SGLT2) inhibitors improve glycemia, weight, and cardiometabolic risk in type 2 diabetes mellitus (T2DM). Head-to-head data comparing empagliflozin with dapagliflozin in South Asian routine care are limited. Objective: To compare the glycemic efficacy and safety of empagliflozin versus dapagliflozin as add-on therapy in adults with inadequately controlled T2DM receiving background oral agents. Methods: We conducted an open-label, randomized controlled trial at a tertiary public hospital (Department of Medicine, Nishtar Hospital, Multan, Pakistan) from 20 December 2024 to 20 May 2025. Adults aged 30–70 years with T2DM and baseline HbA1c 7.5%–12.0% were randomized 1:1 to empagliflozin 25 mg once daily or dapagliflozin 10 mg once daily, in addition to usual oral therapy (metformin, sulfonylurea, and/or DPP-4 inhibitor), for 24 weeks (N=256; 128 per arm). The primary endpoint was the proportion achieving HbA1c <6.5% at 24 weeks; secondary endpoints included mean change in HbA1c, the proportion achieving HbA1c <7.0%, fasting plasma glucose, body weight, blood pressure, and adverse events. Group comparisons used risk ratios with 95% confidence intervals for categorical outcomes and mean differences (95% CI) with two-sided p-values for continuous outcomes (α=0.05). Results: Baseline characteristics were balanced (mean age 52.6 ± 9.8 years; 54.7% male; mean HbA1c 8.80 ± 0.91%). At 24 weeks, mean HbA1c was 6.98 ± 0.68% with empagliflozin versus 7.28 ± 0.74% with dapagliflozin (between-group mean difference −0.29%, 95% CI −0.42 to −0.16; p<0.001). The primary endpoint (HbA1c <6.5%) was achieved by 37.5% with empagliflozin versus 23.4% with dapagliflozin (risk ratio 1.60, 95% CI 1.09–2.34; p=0.014; number needed to treat ≈7). HbA1c <7.0% occurred in 65.6% versus 53.1% (p=0.047). Weight loss was greater with empagliflozin (−3.1 ± 1.8 kg) than with dapagliflozin (−2.2 ± 1.7 kg); mean difference −0.9 kg (95% CI −1.3 to −0.5; p<0.001). A modest reduction in fasting plasma glucose was observed with empagliflozin (mean difference −5 mg/dL; p=0.040). Safety profiles were similar, with low rates of genital mycotic or urinary infections, rare hypoglycemia (1.6% in each group), no diabetic ketoacidosis, and few discontinuations. The single-center, open-label design and 24-week follow-up limit generalizability and long-term inference. Conclusion: Both SGLT2 inhibitors were effective and well tolerated as add-on therapy; empagliflozin produced greater HbA1c lowering and weight loss than dapagliflozin, supporting its preferential use when tighter glycemic targets and weight reduction are priorities in similar populations.